Use of magnetic powder to effectively improve the performance of sequencing batch reactors (SBRs) in municipal wastewater treatment. (January 2018) - Liu, Yi; Li, Jixiang; Guo, Wenshan; Ngo, Huu Hao; Hu, Jiajun; Gao, Min-tian
Highlights: The effect of magnetic powder addition on the performance of MAS-SBR was studied. Adding magnetic powder could enhance the removal of pollutants and sludge reduction. Magnetic powder addition significantly enriched the microbial diversity. Abstract: This study aims to investigate the effect of adding magnetic powder in the sequencing batch reactor (SBR) on the reactor performance and microbial community. Results indicated that, the magnetic activated sludge sequencing batch reactor (MAS-SBR) had 7.76% and 4.76% higher ammonia nitrogen (NH4 + -N) and chemical oxygen demand (COD) removal efficiencies than that of the conventional SBR (C-SBR). The MAS-SBR also achieved 6.86% sludge reduction compared with the C-SBR. High-throughput sequencing demonstrated that the dominant phyla of both SBRs (present as ≥1% of the sequence reads) were Protebacteria, Bacteroidetes, Chloroflexi, Saccharibacteria, Chlorobi, Firmicutes, Actinobactoria, Acidobacteria, Planctomycetes and unclassified_Bacteria . The relative abundance of Protebacteria and Bacteroidetes simultaneously declined whereas the other 8 phyla increased following the addition of magnetic powder. Adding magnetic powder in the SBR significantly affected the microbial diversity and richness of activated sludge, consequently affecting the reactor performance.